2015
DOI: 10.1007/s00603-015-0844-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance of EVA-Based Membranes for SCL in Hard Rock

Abstract: The bonded property of multi-layered sprayed concrete tunnel linings (SCL) waterproofed with sprayed membranes means that the constituent materials will be exposed to the groundwater without any draining or mechanically separating measures. Moisture properties of the sprayed concrete and membrane materials are therefore important in order to establish the system properties of such linings. Ethyl-vinyl-acetate based sprayed membranes exhibit high water absorption potential under direct exposure to water, but ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
10
0
4
Order By: Relevance
“…Table 1 Lining and interface loading scenarios for different SCL tunnel configurations Field measurements by Holter and Geving (2015) on an SCL tunnel in rock with spray-applied waterproofing found the moisture content of the membrane to vary between 30% and 40%, determined by the moisture properties of the concrete and the membrane, as well as the interfaces between the two materials. Further research by Holter (2016) suggested that high moisture content in the membrane may affect its mechanical properties, e.g. reduce its tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Lining and interface loading scenarios for different SCL tunnel configurations Field measurements by Holter and Geving (2015) on an SCL tunnel in rock with spray-applied waterproofing found the moisture content of the membrane to vary between 30% and 40%, determined by the moisture properties of the concrete and the membrane, as well as the interfaces between the two materials. Further research by Holter (2016) suggested that high moisture content in the membrane may affect its mechanical properties, e.g. reduce its tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The case histories indicated that the sprayed membrane can cope with crack widths equal to its thickness [1]. The recent case studies [10] gave similar results.…”
Section: Note To the Left Figurementioning
confidence: 84%
“…The properties of sprayed-on waterproofing membrane is strongly related to the composition of the mixtures of the waterproofing membrane. The recent results [10] shows that the membrane products with low polymeric content (e.g., below 70 %) exhibit low elasticity and are likely unsuitable for tunnel waterproofing purposes.…”
Section: Note To the Left Figurementioning
confidence: 99%
“…one partially or fully saturated due to water coming through cracks in the primary lining, has considerably lower compressive, tensile and shear stiffness and strength than a 'dry' membrane, i.e. one exposed only to the ambient atmospheric environment without direct contact with water [39]. This will theoretically cause a waterproofing membrane interface that was originally bonded to degrade to unbonded, resulting in significant change in load sharing between the primary and secondary linings.…”
Section: Design Considerationsmentioning
confidence: 99%